Assessment of Adverse Effects of Most Commonly Prescribed Anticancer Drugs in a Tertiary Care Teaching Hospital - Sunny, Salu; Thampi, Athira; J, Johnkennedy; Shetty, Nishitha; Babasahib, Sajeev Kumar; Chacko, Chinju (Indian Journal of Pharmacy Practice)
Background: Chemotherapeutic agents account for high inclination towards adverse drug reactions due to its narrow therapeutic window, increased toxicity and highly complex regimen making pharmacovigilance studies essential in oncology. Aim:The aim of the study is to assess the adverse effects of most commonly prescribed anticancer drugs in a tertiary care teaching hospital and to evaluate its causality, severity and preventability. Materials and methods: A prospective observational study was conducted on 200 patients taking chemotherapy in oncology unit. Patient information was obtained using a data collection form and data was collected using a structured questionnaire. Assessment of adverse drug reactions were analyzed using WHO - UMC causalilty assessment scale, Hartwig -Siegel severity assessment scale and modified schumock and thornton preventability scale. Results: Cyclophosphamide (10.62%) was the most commonly prescribed anticancer drug. A total of 450 ADRs were observed from 109 patients. Females (60.55%) were more prone to ADRs than males. The most frequent adverse reaction was vomiting (10%) followed by anaemia (9.11%), alopecia (7.11%), fatigue (6.67%). WHO causality assessment scale showed 45.78% of the reactions to be “possible”, 40.44% to be “probable”, 12.89% to be “unlikely” and 0.89% to be “certain”. Modified Hartwig and Siegel scale showed most reactions, 54.13% to be mild, 44.95% to be moderate and 0.92% to be severe reactions. According to modified Schumock and Thornton scale, 46.22% of the ADRs were “definitely preventable”, 20.67% were “probably preventable” and 33.11% were “not preventable”. Conclusion: Chemotherapeutic agents are highly associated with adverse reactions. Measures should be undertaken to improve ADR monitoring and reporting, thereby decrease the incidence of ADR, improve patient’s quality of life and ensure safe use of drugs.
Keywords: Chemotherapy; Adverse drug reactions; Causality; Severity; Preventability